PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK FROZEN FOOD TINO’S POTATO DOUNTS DI BEKASI TIMUR - Ibnu Suhada; Anita Maulina (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study is prompted by the declining sales number of Tino's potato donuts frozenfood products. This is related to the intense rivalry that existed throughout the pandemic.Therefore, the effort that Tino's potato donuts frozen food product must be made by increasing. The purpose of this study is to see how promotion and price affect purchasingdecisions for Tino's Potato Donuts Frozen Food Products. The studymethod used is a quantitative method. The data collection method is by using in the form of questionnairesand literature. The sample population of this study is theCustomer of Tino's potato donuts frozen food in East Bekasi. The sampling method used in this study is random sampling with the population sampling method. There are 225 samples in all. The Analysis data use multiple linear regression analysis using IBM Statistic software version 25. The findings showthat promotions and prices have a major impact on purchasing decisions. Promotion and Price affect the Purchasing Decision variable simultaneously with a value of 0.691 or 69.1% of which 30.9% is explained by other factors not included in this study.